2020
DOI: 10.3390/cancers12123790
|View full text |Cite
|
Sign up to set email alerts
|

Commercialized Blood-, Urinary- and Tissue-Based Biomarker Tests for Prostate Cancer Diagnosis and Prognosis

Abstract: In the diagnosis and prognosis of prostate cancer (PCa), the serum prostate-specific antigen test is widely used but is associated with low specificity. Therefore, blood-, urinary- and tissue-based biomarker tests have been developed, intended to be used in the diagnostic and prognostic setting of PCa. This review provides an overview of commercially available biomarker tests developed to be used in several clinical stages of PCa management. In the diagnostic setting, the following tests can help selecting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 104 publications
1
18
0
Order By: Relevance
“…Previous reports demonstrated that PCA3 was present in urine and could be a diagnostic marker for prostate cancer [19][20][21]. A recent meta-analysis of PCA3 including 54 studies (17,575 patients) indicated that the overall ROC of PCA3 was 0.75 (95% CI: 0.71-0.79) [22].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports demonstrated that PCA3 was present in urine and could be a diagnostic marker for prostate cancer [19][20][21]. A recent meta-analysis of PCA3 including 54 studies (17,575 patients) indicated that the overall ROC of PCA3 was 0.75 (95% CI: 0.71-0.79) [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, our PCA indeed uncover relevant PRAD genes found dispersed across several studies, providing new putative biomarkers and/or drivers. In this sense, the inclusion of PCA3 within our PRAD-CES seems encouraging since this LncRNA is well recognized as causative, prostate-specific and feasible biomarker which is secreted to an easy-to-inquire biological fluids [65]. Finally, as therapeutic options for poorly tractable Pca are limited, the evaluation of putative novel molecular targets populating PRAD-CES seems appealing.…”
Section: Discussionmentioning
confidence: 99%
“…Different trials have focused on improving “smart screening” through PSA‐derived blood tests (4Kscore, PHI) and postDRE urine‐based gene assays (MiPS, Select MDx). However, most of these tests have not been tested in the gray‐zone (the most uncertain risk population) cohorts of biopsy‐naïve patients with a normal DRE and a PSA between 3 and 10 ng/ml 9 . Furthermore, current clinical practice guidelines strongly recommend performing prostatic magnetic resonance imaging (pMRI) before a prostate biopsy, as pMRI has shown high sensitivity for the identification of Sig PCa.…”
Section: Introductionmentioning
confidence: 99%